Respons tomat (Solanum lycopersicum l.) terhadap KH₂PO₄ dan giberelin pada hidroponik dutch bucket: Tomato (Solanum lycopersicum l.) hydroponics: effects of KH₂PO₄ and gibberellin - Maghfirah, Intan Hadiatun; Fanata, Wahyu Indra Duwi; Sholikhah, Ummi; Saputra, Tri Wahyu (Jurnal AGRO, 2025)
Tomato (Solanum lycopersicum L.) is a horticultural commodity which the quality and the yield can be enhanced through the application of the Dutch bucket hydroponic system, along with KH₂PO₄ fertilization and gibberellin hormone treatments. This study aimed to evaluate the response of tomato plants in terms of productivity and quality under these treatments. The experiment was conducted in a greenhouse using factorial randomized complete block design with three replications. The first factor was KH₂PO₄ concentration at three levels: 0 ppm, 150 ppm, and 250 ppm; the second factor was gibberellin concentration at three levels: 0 ppm, 50 ppm, and 100 ppm. Data were analyzed using ANOVA and DMRT on parameters including number of flowers, number of fruits per plant, fruit diameter, average fruit weight, total fruit weight per plant, and total soluble solids value. The results indicated that the interaction of 150 ppm KH₂PO₄ and 50 ppm gibberellin produced optimal values for fruit weight per fruit of 41.32 g, total fruit weight per plant of 398.67 g, and total soluble solids of 6.28 °Bx. Furthermore, either individual effects of KH₂PO₄ or gibberellin concentrations significantly influenced all observed variables except on fruit diameter. Combination KH2PO4 150 ppm and gibbereilin 50 ppm is recommended for enhancing tomato cultivation performance under the Dutch bucket hydroponic system. ABSTRAK Tomat (Solanum lycopersicum L.) merupakan komoditas hortikultura yang kualitas dan produksinya dapat ditingkatkan melalui penerapan sistem hidroponik Dutch bucket disertai penggunaan pupuk KH₂PO₄ dan hormon giberelin. Penelitian ini bertujuan untuk mengetahui respons tanaman tomat khususnya pada produktivitas dan kualitas terkait perlakuan tersebut. Penelitian dilakukan di dalam greenhouse menggunakan rancangan acak kelompok (RAK) faktorial dengan 3 ulangan. Faktor pertama adalah konsentrasi KH₂PO₄ dengan tiga taraf yaitu 0 ppm, 150 ppm, dan 250 ppm, faktor kedua adalah konsentrasi giberelin dengan tiga taraf yaitu 0 ppm, 50 ppm, dan 100 ppm. Data dianalisis menggunakan ANOVA dan DMRT dengan variabel pengamatan meliputi jumlah bunga, jumlah buah per tanaman, diameter buah, bobot per buah, bobot buah per tanaman, dan total padatan terlarut. Hasil penelitian menunjukkan interaksi antara KH₂PO₄ 150 ppm dan giberelin 50 ppm memberikan hasil terbaik pada variabel bobot per buah sebesar 41,32 g, bobot buah per tanaman sebesar 398,67 g, dan total padatan terlarut sebesar 6,28 °Bx. Selanjutnya, pengaruh faktor tunggal konsentrasi KH₂PO₄ maupun konsentrasi giberelin memberikan pengaruh pada seluruh variabel yang diamati kecuali diameter buah. Penggunaan KH2PO4 150 ppm dan giberelin 50 ppm dapat menjadi rekomendasi terbaik untuk diaplikasikan pada budidaya tomat menggunakan sistem Dutch bucket. Kata kunci: Dutch bucket, giberelin, hidroponik, KH2PO4, tomat